Paralytic shellfish toxin profiles in mussel, cockle and razor shell under post-bloom natural conditions: evidence of higher biotransformation in razor shells and cockles - Botelho, Maria João (2020)
Concentrations of the paralytic shellfish toxins GTX6, C1+2, GTX5, C3+4, dcSTX, dcNEO and dcGTX2+3 were determined by LC-FLD in composite samples of whole soft tissues of mussels (Mytilus galloprovincialis), cockles (Cerastoderma edule) and razor shells (Solen marginatus) after exposure to a Gymnodinium catenatum bloom. Specimens were harvested weekly during three months under natural depuration conditions in the Mira branch of Aveiro lagoon, Portugal. Under the decline of G. catenatum cell densities, elimination or transformation of the uptake toxins associated with the ingestion of toxic cells differed among the surveyed species. Ratio between the toxins dcSTX plus dcGTX2+3 plus dcNEO and toxins GTX6 plus GTX5 plus C1+2 plus C3+4 was used to illustrate the biotransformation occurring in the bivalves. Enhancement of the ratios was observed for razor shells and cockles seven weeks after the peak of the algal bloom. Most likely it reflects more intense biotransformation in razor shells and cockles than in mussels. Conversion into toxins of higher toxicity may prolong the bivalve toxicity. These results show the complexity of toxin elimination in bivalves under post-bloom conditions and emphasize the pertinence of monitoring programs of bivalve toxicity in order to protect human health.